Evolution of diverse effective N2-fixing microsymbionts of Cicer arietinum following horizontal transfer of the Mesorhizobium ciceri CC1192 symbiosis integrative and conjugative element. - Hill, Yvette; Colombi, Elena; Bonello, Emma; Haskett, Timothy; Ramsay, Josh; O'Hara, Graham; Terpolilli, Jason (2020)
Rhizobia are soil bacteria capable of forming N2-fixing symbioses with legumes, with highly effective strains often selected in agriculture as inoculants to maximize symbiotic N2 fixation. When rhizobia in the genus Mesorhizobium have been introduced with exotic legumes into farming systems, horizontal transfer of symbiosis Integrative and Conjugative Elements (ICEs) from the inoculant strain to soil bacteria has resulted in the evolution of ineffective N2-fixing rhizobia that are competitive for nodulation with the target legume. In Australia, Cicer arietinum (chickpea) has been inoculated since the 1970's with Mesorhizobium ciceri sv. ciceri CC1192, a highly effective strain from Israel. Although the full genome sequence of this organism is available, little is known about the mobility of its symbiosis genes and the diversity of cultivated C. arietinum-nodulating organisms. Here, we show the CC1192 genome harbors a 419-kb symbiosis ICE (ICEMcSym1192) and a 648-kb repABC-type plasmid pMC1192 carrying putative fix genes. We sequenced the genomes of 11 C. arietinum nodule isolates from a field site exclusively inoculated with CC1192 and showed they were diverse unrelated Mesorhizobium carrying ICEMcSym1192, indicating they had acquired the ICE by environmental transfer. No exconjugants harboured pMc1192 and the plasmid was not essential for N2 fixation in CC1192. Laboratory conjugation experiments confirmed ICEMcSym1192 is mobile, integrating site-specifically within the 3' end of one of the four ser-tRNA genes in the R7ANS recipient genome. Strikingly, all ICEMcSym1192 exconjugants were as efficient at fixing N2 with C. arietinum as CC1192, demonstrating ICE transfer does not necessarily yield ineffective microsymbionts as previously observed.Importance Symbiotic N2 fixation is a key component of sustainable agriculture and in many parts of the world legumes are inoculated with highly efficient strains of rhizobia to maximise fixed N2 inputs into farming systems. Symbiosis genes for Mesorhizobium spp. are often encoded chromosomally within mobile gene clusters called Integrative and Conjugative Elements or ICEs. In Australia, where all agricultural legumes and their rhizobia are exotic, horizontal transfer of ICEs from inoculant Mesorhizobium strains to native rhizobia has led to the evolution of inefficient strains that outcompete the original inoculant, with the potential to render it ineffective. However, the commercial inoculant strain for Cicer arietinum (chickpea), M. ciceri CC1192, has a mobile symbiosis ICE (ICEMcSym1192) which can support high rates of N2 fixation following either environmental or laboratory transfer into diverse Mesorhizobium backgrounds, demonstrating ICE transfer does not necessarily yield ineffective microsymbionts as previously observed.